Au-quasi UiO-66 composite material, preparation method thereof and application of Au-quasi UiO-66 composite material in photocatalytic CO2 cycloaddition
By constructing Au@ quasi-UiO-66 composite materials with multi-stage pore MOFs encapsulated metal nanoparticles, the problem of difficult to achieve high-efficiency photocatalytic cycloaddition reaction between CO2 and epoxide under low concentrations in the prior art is solved, and the effect of efficient photoco-catalytic and cost reduction is achieved.
Patent Information
- Application Number
- CN202411639737.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to achieve efficient photocatalytic cycloaddition reaction between CO2 and epoxide under low concentrations of CO2, and it is difficult to accurately regulate the metal load in UiO-66 during the preparation process, which has the problem of high economic costs.
By constructing multi-stage pore MOFs encapsulated metal nanoparticles, using Au@ quasi-UiO-66 composite material, the plasmon resonance effect of bimetallic nanoparticles, the mutual coordination of Lewis acid active position and MOFs multi-stage pores, the efficient photo-coordinated catalyzed cycloaddition reaction between CO2 and epoxides is achieved.
High-efficiency photocatalytic CO2 cycloaddition reaction with epoxide under low concentration CO2 conditions is achieved, which improves the utilization efficiency and catalytic performance of light and reduces the preparation cost.
Smart Images

Figure CN119771496A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nano material preparation and application, and in particular to an Au@quasi-UiO-66 composite material and a preparation method thereof and application in photocatalytic CO2 cycloaddition. Background Art
[0002] Energy is the cornerstone of social progress and industrial development. However, the direct consumption of primary fossil energy has led to a large amount of carbon (CO2) emissions, bringing severe energy and environmental problems. The use of photocatalytic technology to directly convert low-concentration CO2 (5-15%) contained in industrial waste gas into chemical raw materials or carbon-based fuels under the drive of solar energy provides a very potential solution for the utilization of renewable carbon resources. The emitted CO2 can be recycled and reused in new production processes, which can effectively reduce the CO2 content in the atmosphere. Therefore, achieving efficient photocatalytic CO2 conversion under low-concentration CO2 conditions is of great significance for the resource utilization of CO2 and environmental protection in industrial waste gas and other environments.
[0003] MOFs materials are a type of porous crystalline materials connected by metal ions or metal clusters and organic ligands. Due to their high designability and modifiability, high specific surface area and high porosity, they show good application prospects in the capture and separation of CO2 and its chemical conversion. However, the functions of MOFs materials with a single structure are greatly limited, making it difficult to achieve efficient photocatalytic low-concentration CO2 and epoxide cycloaddition reactions. Designing and preparing multifunctional MOFs composite materials and organically combining multiple properties and functions is expected to expand their application in the field of efficient photocatalytic low-concentration CO2 and epoxide cycloaddition.
[0004] For example, Huang et al. successfully introduced Lewis acid Bi atoms into the porphyrin ring of the metal organic framework (PCN-224) to synthesize Bi-PCN-224. Under light, Bi-PCN-224 undergoes a charge transfer process from Bi porphyrin to Zr, converting Zr(IV) to Zr(III), which can further activate CO2. At the same time, the holes generated by light can enhance the Lewis acidity of the system and further promote the ring-opening reaction of propylene oxide. Under light conditions, it can efficiently catalyze the cycloaddition of CO2 and epoxides, with a conversion rate and selectivity of up to 99% and 100% for the cycloaddition of propylene oxide and CO2, respectively. [Guang-yao Zhai, Yuan-yuan Liu, Long-fei Lei, Jia-jia Wang, Ze-yan Wang, Zhao-ke Zheng, Peng Wang, He-feng Cheng, Ying Dai, Bai-biao Huang. Light-Promoted CO2 Conversion from Epoxides to CyclicCarbonates at Ambient Conditions over a Bi-Based Metal-Organic Framework[J].ACS Catal.2021,11,1988-1994].
[0005] Chinese patent CN 113769789 B discloses a method for preparing a UiO-66 defect-induced single-atom supported catalyst and its application. The patent is to add a metal source and UiO-66 to distilled water, disperse them evenly by ultrasonication for 1 hour, and continuously introduce an inert gas into the reactor at a rate of 40 mL / min for 30 minutes under dark conditions, place it under ultraviolet light, and control the reactor temperature to 25°C by circulating water for 0.5-10 hours. After the reaction is completed, the obtained mixture is washed with distilled water, centrifuged, and the lower layer of the centrifuged product is vacuum dried to obtain the target product. However, in the preparation process, it is difficult to accurately control the metal loading in UiO-66, and a large amount of loss is inevitable, especially for precious metals, which is economically expensive.
[0006] Chinese patent CN 107233924 B discloses the preparation and application of thiol-modified metal organic framework compound catalysts. The patent is to dissolve zirconium tetrachloride and 2,5-dimercapto-1,4-terephthalic acid in N,N-dimethylformamide solution and mix them evenly, keep them at 120℃ for 24h, centrifuge and dry them to obtain UiO-66(SH)2 photocatalyst; UiO-66(SH)2 photocatalyst is fully mixed with appropriate amount of HAuCl4, H2PdCl4, H2PtCl6 solution, stirred for 12h, filtered, washed and dried to obtain M / UiO-66(SH)2 composite photocatalyst, wherein M is one of Au, Pd and Pt. However, in actual operation, the proportion of active components in the catalyst is not easy to control, which may lead to differences in catalytic effect. Summary of the invention
[0007] In order to overcome at least one of the shortcomings and deficiencies of the above-mentioned prior art, the present invention aims to develop a method for preparing an Au@quasi-UiO-66 composite material by pyrolysis using UiO-66 as a template and its application in visible light catalytic CO2 cycloaddition. The present invention realizes efficient photocatalytic cycloaddition reaction under low CO2 concentration conditions by constructing multi-level pore MOFs to encapsulate metal nanoparticles. This type of catalyst can be regulated by IB group metals (Cu, Ag, Au) with strong surface plasmon resonance effect through the unique electronic effect in bimetallic nanoparticles, so that it has a wide absorption in the visible light region; the rich pore structure in the MOFs framework can improve the enrichment of CO2 in the material, and the Lewis acid active sites and halogen ions are conducive to the activation of CO2 and the ring opening of epoxides. The plasma resonance effect of bimetallic nanoparticles, Lewis acid, Lewis base active sites and the mutual synergy of MOFs multi-level pores can realize efficient photosynergistic catalytic CO2 and epoxide cycloaddition to prepare cyclic carbonates.
[0008] The purpose of the present invention is achieved based on the following technical solutions:
[0009] The first aspect of the present invention provides a method for preparing an Au@quasi-UiO-66 composite material, comprising the following steps:
[0010] S1. Preparation of UiO-66 materials;
[0011] S2, adding the obtained UiO-66 material and [Bmim][AuCl4] into anhydrous methanol for ultrasonic mixing, and stirring evenly to obtain a mixed solution;
[0012] S3, mixing and stirring the obtained mixed solution evenly, then rotary evaporating and vacuum drying to obtain [Bmim][AuCl4]@UiO-66 material;
[0013] S4. The obtained [Bmim][AuCl4]@UiO-66 is pyrolyzed in a hydrogen-argon mixed gas atmosphere to obtain an Au@quasi-UiO-66 composite material.
[0014] During the pyrolysis process of the composite material of the present invention, the ionic liquid is completely pyrolyzed due to the low pyrolysis temperature, while the crystallinity of UiO-66 remains intact. However, during the pyrolysis process, the residual solvent and excess ligands in UiO-66 will be pyrolyzed. With reference to other people's articles, it is named quasi-UiO-66.
[0015] Preferably, the preparation of the UiO-66 material in step S1 comprises the following steps:
[0016] S11, adding ZrOCl2·8H2O to N,N-dimethylformamide and dissolving it by ultrasonication to obtain a metal salt solution; adding terephthalic acid to N,N-dimethylformamide and dissolving it by ultrasonication to obtain an organic ligand solution;
[0017] S12, mixing the obtained metal salt solution with the organic ligand solution, adding formic acid after mixing, mixing evenly by ultrasonication, stirring and reacting at 100-130° C. for a period of time, centrifuging and separating the solid product after cooling, washing, and drying to obtain UiO-66 material.
[0018] Preferably, in step S11:
[0019] The molar concentration of ZrOCl2·8H2O in the metal salt solution is 0.5-1.0 mol / L;
[0020] The molar concentration of terephthalic acid in the organic ligand solution is 0.5 to 1.5 mol / L;
[0021] The organic ligand and the metal salt are dissolved in the solvent by ultrasound, and the ultrasound time is 5 to 30 minutes.
[0022] Preferably, in step S12, the stirring reaction time is 2 to 6 hours.
[0023] Preferably, in step S2:
[0024] The molar concentration of [Bmim][AuCl4] in the mixed solution is 0.0025-0.050 mol / L;
[0025] The solvent is stirred at a temperature of 10 to 40°C for 18 to 24 hours;
[0026] Preferably, in step S2, the mass ratio of the ionic liquid to the porous nano-carbon material is 0.05 to 0.15, more preferably 0.05 to 0.125.
[0027] Preferably, in step S3:
[0028] The mixing time is 18 to 24 hours, and the temperature is 10 to 40°C;
[0029] The rotary evaporation temperature is 50-70°C and the rotary evaporation time is 1-2h;
[0030] The drying is vacuum drying, and the vacuum drying temperature is 60-100°C.
[0031] Preferably, in step S4, the pyrolysis temperature is 325-450° C., and the pyrolysis time is 1-4 hours.
[0032] The second aspect of the present invention provides an Au@quasi-UiO-66 composite material prepared according to the above preparation method.
[0033] The third aspect of the present invention provides an application of an Au@quasi-UiO-66 composite material in the photocatalytic cycloaddition reaction of CO2 and epoxide at room temperature.
[0034] Preferably, the application method is: mixing the obtained Au@quasi-UiO-66 composite material with an epichlorohydrin solution, introducing CO2, and performing a cycloaddition reaction under light.
[0035] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0036] 1. The preparation method of the present invention is simple and quick to operate, green and environmentally friendly, and low in cost.
[0037] 2. The present invention prepares Au@quasi-UiO-66 composite material by directly pyrolyzing [Bmim][AuCl4]@UiO-66, which has ultra-high specific surface area and more active sites, can carry out CO2 and epoxide cycloaddition reaction under light irradiation conditions, and has high energy conversion efficiency; the Au@quasi-UiO-66 composite material obtained by the present invention has excellent photothermal conversion performance, can greatly improve the utilization efficiency of light and improve the catalytic performance.
[0038] 3. The Au@quasi-UiO-66 composite material prepared by the present invention has excellent catalytic performance in the photocatalytic CO2 and epoxide cycloaddition reaction, strong applicability, and good practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The XRD pattern of the Au@quasi-UiO-66 composite material obtained in Example 3;
[0040] Figure 2 This is a N2 adsorption-desorption curve of the Au@quasi-UiO-66 composite material obtained in Example 3;
[0041] Figure 3 This is a performance diagram of the Au@quasi-UiO-66 composite material obtained in Example 3 in catalyzing the cycloaddition reaction of CO2 and epoxide under visible light. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] [Bmim][AuCl4] used in the following examples was obtained by the preparation method in the invention patent application number 202110050450.1.
[0044] Example 1
[0045] In this embodiment, Au@quasi-UiO-66 composite material is prepared by direct pyrolysis of [Bmim][AuCl4]@UiO-66 and applied in photocatalytic CO2 cycloaddition reaction:
[0046] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0047] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0048] (3) Weigh the UiO-66 material (100 mg) obtained in step (2) and [Bmim][AuCl4] (5 mg), add them to anhydrous methanol (20 mL), mix them by ultrasonication for 15 min, stir them at 25 ° C for 24 h, rotary evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;
[0049] (4) Weigh the [Bmim][AuCl4]@UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 375°C for 2 h, cool it to room temperature and then take it out. The obtained 1#Au@quasi-UiO-66 material can be used directly.
[0050] (5) Weigh the 1#Au@quasi-UiO-66 composite material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.
[0051] Example 2
[0052] In this embodiment, Au@quasi-UiO-66 composite material is prepared by direct pyrolysis of [Bmim][AuCl4]@UiO-66 and applied in photocatalytic CO2 cycloaddition reaction:
[0053] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0054] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0055] (3) Weigh the UiO-66 material (100 mg) obtained in step (2) and [Bmim][AuCl4] (7.5 mg), add them to anhydrous methanol (20 mL), mix them evenly by ultrasonication for 15 min, stir at 25 ° C for 24 h, rotary evaporate at 60 ° C for 1 h, and vacuum dry for 12 h to obtain a composite material;
[0056] (4) Weigh the [Bmim][AuCl4]@UiO-66 (100 mg) obtained in step (3), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 375°C for 2 h, cool it to room temperature and then take it out. The obtained 2#Au@quasi-UiO-66 material can be used directly.
[0057] (5) Weigh the 2#Au@quasi-UiO-66 composite material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.
[0058] Example 3
[0059] In this embodiment, Au@quasi-UiO-66 composite material is prepared by direct pyrolysis of [Bmim][AuCl4]@UiO-66 and applied in photocatalytic CO2 cycloaddition reaction:
[0060] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0061] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0062] (3) Weigh the UiO-66 material (100 mg) obtained in step (2) and [Bmim][AuCl4] (10 mg), add them to anhydrous methanol (20 mL), mix them by ultrasonication for 15 min, stir them at 25 ° C for 24 h, rotary evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;
[0063] (4) Weigh the [Bmim][AuCl4]@UiO-66 (100 mg) obtained in step (3), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 375°C for 2 h, cool it to room temperature and then take it out. The obtained 3#Au@quasi-UiO-66 material can be used directly.
[0064] (5) Weigh the 3#Au@quasi-UiO-66 composite material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.
[0065] Example 4
[0066] In this embodiment, Au@quasi-UiO-66 composite material is prepared by direct pyrolysis of [Bmim][AuCl4]@UiO-66 and applied in photocatalytic CO2 cycloaddition reaction:
[0067] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0068] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0069] (3) Weigh the UiO-66 material (100 mg) obtained in step (2) and [Bmim][AuCl4] (12.5 mg), add them to anhydrous methanol (20 mL), mix them by ultrasonication for 15 min, stir them at 25 ° C for 24 h, evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;
[0070] (4) Weigh the [Bmim][AuCl4]@UiO-66 (100 mg) obtained in step (3), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 375°C for 2 h, cool it to room temperature and then take it out. The obtained 4#Au@quasi-UiO-66 material can be used directly.
[0071] (5) Weigh the 4#Au@quasi-UiO-66 composite material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.
[0072] Example 5
[0073] In this embodiment, Au@quasi-UiO-66 composite material is prepared by direct pyrolysis of [Bmim][AuCl4]@UiO-66 and applied in photocatalytic CO2 cycloaddition reaction:
[0074] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0075] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0076] (3) Weigh the UiO-66 material (100 mg) obtained in step (2) and [Bmim][AuCl4] (15 mg), add them to anhydrous methanol (20 mL), mix them by ultrasonication for 15 min, stir them at 25 ° C for 24 h, rotary evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;
[0077] (4) Weigh the [Bmim][AuCl4]@UiO-66 (100 mg) obtained in step (3), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 375°C for 2 h, cool it to room temperature and take it out. The obtained 5#Au@quasi-UiO-66 material can be used directly.
[0078] (5) Weigh the 5#Au@quasi-UiO-66 composite material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.
[0079] Example 6
[0080] In this embodiment, Au@quasi-UiO-66 composite material is prepared by direct pyrolysis of [Bmim][AuCl4]@UiO-66 and applied in photocatalytic CO2 cycloaddition reaction:
[0081] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0082] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0083] (3) Weigh the UiO-66 material (100 mg) obtained in step (2) and [Bmim][AuCl4] (10 mg), add them to anhydrous methanol (20 mL), mix them by ultrasonication for 15 min, stir them at 25 ° C for 24 h, rotary evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;
[0084] (4) Weigh the [Bmim][AuCl4]@UiO-66 (100 mg) obtained in step (3), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 350°C for 2 h, cool it to room temperature and then take it out. The obtained 6#Au@quasi-UiO-66 material can be used directly.
[0085] (5) Weigh the 6#Au@quasi-UiO-66 composite material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.
[0086] Example 7
[0087] In this embodiment, Au@quasi-UiO-66 composite material is prepared by direct pyrolysis of [Bmim][AuCl4]@UiO-66 and applied in photocatalytic CO2 cycloaddition reaction:
[0088] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0089] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0090] (3) Weigh the UiO-66 material (100 mg) obtained in step (2) and [Bmim][AuCl4] (10 mg), add them to anhydrous methanol (20 mL), mix them by ultrasonication for 15 min, stir them at 25 ° C for 24 h, rotary evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;
[0091] (4) Weigh the [Bmim][AuCl4]@UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 400°C for 2 h, cool it to room temperature and then take it out. The obtained 7#Au@quasi-UiO-66 material can be used directly.
[0092] (5) Weigh the 7#Au@quasi-UiO-66 composite material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.
[0093] Example 8
[0094] In this embodiment, Au@quasi-UiO-66 composite material is prepared by direct pyrolysis of [Bmim][AuCl4]@UiO-66 and applied in photocatalytic CO2 cycloaddition reaction:
[0095] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0096] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0097] (3) Weigh the UiO-66 material (100 mg) obtained in step (2) and [Bmim][AuCl4] (10 mg), add them to anhydrous methanol (20 mL), mix them by ultrasonication for 15 min, stir them at 25 ° C for 24 h, rotary evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;
[0098] (4) Weigh the [Bmim][AuCl4]@UiO-66 (100 mg) obtained in step (3), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 425°C for 2 h, cool it to room temperature and then take it out. The obtained 8#Au@quasi-UiO-66 material can be used directly.
[0099] (5) Weigh the 8#Au@quasi-UiO-66 composite material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.
[0100] The powder diffraction results of the Au@quasi-UiO-66 composite material obtained in Example 3 are as follows: Figure 1As shown in FIG. 1 , the sample shows the characteristic peak of Au phase, and the characteristic peak of Au phase is weak, indicating that the Au content in the composite material prepared by the present invention is low or the size is small. The nitrogen adsorption-desorption curve of the Au@quasi-UiO-66 composite material obtained in Example 3 is shown in FIG. Figure 2 As shown in the figure, it can be seen that Au@quasi-UiO-66 has an ultra-high specific surface area, which is conducive to the enrichment of CO2 in the material. Example 3 Preparation of Au@quasi-UiO-66 composite material by direct pyrolysis of [Bmim][AuCl4]@UiO-66 and application in photocatalytic CO2 cycloaddition reaction: The performance test results of the material in catalyzing the cycloaddition reaction of CO2 and epoxide under visible light are shown in Figure 3 The results show that the reaction performance of the material obtained by pyrolysis at a suitable temperature is significantly enhanced, and a conversion rate of 96% and a selectivity of 99% can be achieved within 6 hours, indicating that the Au@quasi-UiO-66 composite material can greatly improve the utilization efficiency of light and improve the catalytic performance.
[0101] 1. The AAS test (atomic absorption) results of the Au@quasi-UiO-66 composite materials obtained in Examples 1 to 8 are shown in Table 1:
[0102] Table 1
[0103] sample AAS (Cowt%) 1#Au@quasi-UiO-66 2.1% 2#Au@quasi-UiO-66 2.7% 3#Au@quasi-UiO-66 3.4% 4#Au@quasi-UiO-66 4.1% 5#Au@quasi-UiO-66 4.9% 6#Au@quasi-UiO-66 2.9% 7#Au@quasi-UiO-66 3.3% 8#Au@quasi-UiO-66 3.4%
[0104] It can be seen from the results in Table 1 that the preferred embodiments of the present invention all obtained Au-containing composite nanomaterials.
[0105] 2. The performance of the Au@quasi-UiO-66 composite material obtained in Examples 1 to 8 in catalyzing the cycloaddition of CO2 and epichlorohydrin to generate 1,3-dioxolane-2-one, 4-chloromethyl under light was tested. The results are listed in Table 2.
[0106] Table 2
[0107] sample 6h conversion rate 2h Selective 1#Au@quasi-UiO-66 64% 99% 2#Au@quasi-UiO-66 79% 99% 3#Au@quasi-UiO-66 96% 99% 4#Au@quasi-UiO-66 83% 99% 5#Au@quasi-UiO-66 78% 99% 6#Au@quasi-UiO-66 82% 99% 7#Au@quasi-UiO-66 79% 99% 8#Au@quasi-UiO-66 73% 99%
[0108] The experimental conditions for the catalytic reaction were as follows: catalyst (10 mg), epichlorohydrin (0.1 mmol), tetrabutylammonium bromide (0.1 mmol), N,N-dimethylformamide (2 mL), 300 mWcm -2 Full spectrum radiation, excess CO2, reaction time 6h.
[0109] As can be seen from the data in Table 2, the Au@quasi-UiO-66 composite material prepared by the present invention has good catalytic activity in the catalytic CO2 and epoxide cycloaddition reaction under illumination, and can reach a conversion rate of ≥64% and a selectivity of 99% within 6 hours, indicating that the Au@quasi-UiO-66 composite material can improve the photothermal conversion performance, accelerate the mass transfer rate, and improve the catalytic performance; the reaction selectivity is 99%, indicating that there are almost no by-products in the reaction. Among them, the Au@quasi-UiO-66 material obtained in Example 3 has the best result in the CO2 and epoxide cycloaddition reaction performance test, and can reach a conversion rate of 96% and a selectivity of 99% within 6 hours, indicating that the prepared Au@quasi-UiO-66 composite material has significantly enhanced reaction performance.
[0110] Comparative Example 1 ([Bmim][AuCl4] is not added in step 3)
[0111] This comparative example provides a method for preparing UiO-66-375 material, comprising the following steps:
[0112] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0113] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0114] (3) Weigh the UiO-66 material (100 mg) obtained in step (2), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed atmosphere at 375° C. for 2 h, cool it to room temperature and take it out to obtain the UiO-66-375 material which can be used directly.
[0115] (4) Weigh the UiO-66-375 composite material (10 mg) obtained in step (3), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.
[0116] The UiO-66-375 material prepared in Comparative Example 1 catalyzes the cycloaddition reaction of CO2 and epoxide under the same conditions as the 3#Au@quasi-UiO-66 material prepared in Example 3, with a conversion rate of 9% and a selectivity of 99%.
[0117] Comparative Example 2 (HAuCl4 was added in step 3)
[0118] This comparative example provides a method for preparing Au / quasi-UiO-66 material, comprising the following steps:
[0119] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0120] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0121] (3) Weigh the UiO-66 material (100 mg) obtained in step (2) and HAuCl4 (7.5 mg), add them to anhydrous methanol (20 mL), mix them evenly by ultrasonication for 15 min, stir at 25 ° C for 24 h, rotary evaporate at 60 ° C for 1 h, and vacuum dry for 12 h to obtain a composite material;
[0122] (4) Weigh HAuCl4 / UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 375°C for 2 h, cool it to room temperature and then take it out. The obtained Au / quasi-UiO-66 composite material can be used directly.
[0123] (5) Weigh the Au / quasi-UiO-66 composite material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out cycloaddition reaction under light. Step (3) uses non-ionic liquid, and the rest is the same as Example 3.
[0124] The Au / quasi-UiO-66 material prepared in Comparative Example 2 catalyzed the cycloaddition reaction of CO2 and epoxide under the same conditions as the 3#Au@quasi-UiO-66 material prepared in Example 3, with a conversion rate of 39% and a selectivity of 99%.
[0125] Comparative Example 3 (pyrolysis temperature in step 4 is 250°C)
[0126] This comparative example provides a method for preparing Au@quasi-UiO-66 material, comprising the following steps:
[0127] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0128] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0129] (3) Weigh the UiO-66 material (100 mg) obtained in step (2) and [Bmim][AuCl4] (10 mg), add them to anhydrous methanol (20 mL), mix them by ultrasonication for 15 min, stir them at 25 ° C for 24 h, rotary evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;
[0130] (4) Weigh the [Bmim][AuCl4]@UiO-66 (100 mg) obtained in step (3), put it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 250°C for 2 h, cool it to room temperature and then take it out. The obtained Au@quasi-UiO-66 material can be used directly.
[0131] (5) Weigh the Au@quasi-UiO-66 composite material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.
[0132] The Au / quasi-UiO-66 material prepared in Comparative Example 3 catalyzed the cycloaddition reaction of CO2 and epoxide under the same conditions as the 3#Au@quasi-UiO-66 material prepared in Example 3, with a conversion rate of 5% and a selectivity of 99%.
[0133] Comparative Example 4 (pyrolysis temperature in step 4 is 500°C)
[0134] This comparative example provides a method for preparing Au@quasi-UiO-66 material, comprising the following steps:
[0135] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0136] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0137] (3) Weigh the UiO-66 material (100 mg) obtained in step (2) and [Bmim][AuCl4] (10 mg), add them to anhydrous methanol (20 mL), mix them by ultrasonication for 15 min, stir them at 25 ° C for 24 h, rotary evaporate them at 60 ° C for 1 h, and vacuum dry them for 12 h to obtain a composite material;
[0138] (4) Weigh the [Bmim][AuCl4]@UiO-66 (100 mg) obtained in step (3), send it into a tubular furnace for pyrolysis in a hydrogen-argon mixed gas atmosphere at 500°C for 2 h, cool it to room temperature and then take it out. The obtained Au@quasi-UiO-66 material can be used directly.
[0139] (5) Weigh the Au@quasi-UiO-66 composite material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.
[0140] The Au@quasi-UiO-66 material prepared in Comparative Example 4 catalyzes the cycloaddition reaction of CO2 and epoxide under the same conditions as the Au@quasi-UiO-66 material prepared in Example 3, with a conversion rate of 19% and a selectivity of 99%.
[0141] By comparing the catalytic performance results of the above comparative example with those of Example 3, it was found that the Au@quasi-UiO-66 composite material obtained by direct pyrolysis of [Bmim][AuCl4]@UiO-66 in Example 3 had excellent performance in catalyzing the cycloaddition reaction of CO2 and epoxide under light, and had good practical application value.
[0142] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an Au@quasi-UiO-66 composite material, characterized in that: The following steps are involved: S1. Preparation of UiO-66 materials; S2, adding the obtained UiO-66 material and [Bmim][AuCl4] into anhydrous methanol for ultrasonic mixing, and stirring evenly to obtain a mixed solution; S3, mixing and stirring the obtained mixed solution evenly, and then rotary evaporating and drying to obtain [Bmim][AuCl4]@UiO-66 material; S4. The obtained [Bmim][AuCl4]@UiO-66 is pyrolyzed in a hydrogen-argon mixed gas atmosphere to obtain an Au@quasi-UiO-66 composite material.
2. The method for preparing the Au@quasi-UiO-66 composite material according to claim 1, characterized in that: The preparation of the UiO-66 material in step S1 comprises the following steps: S11, adding ZrOCl2·8H2O to a solvent and dissolving it by ultrasonication to obtain a metal salt solution; adding terephthalic acid to a solvent and dissolving it by ultrasonication to obtain an organic ligand solution; S12, mixing the obtained metal salt solution with the organic ligand solution, adding formic acid after mixing, mixing evenly by ultrasonication, stirring and reacting at 100-130° C. for a period of time, centrifuging and separating the solid product after cooling, washing, and drying to obtain UiO-66 material.
3. The method for preparing the Au@quasi-UiO-66 composite material according to claim 2, characterized in that: In the step S11: The molar concentration of ZrOCl2·8H2O in the metal salt solution is 0.5-1.0 mol / L; The molar concentration of terephthalic acid in the organic ligand solution is 0.5 to 1.5 mol / L; The organic ligand and the metal salt are dissolved in the solvent by ultrasound, and the ultrasound time is 5 to 30 minutes; The solvent is N,N-dimethylformamide.
4. The method for preparing the Au@quasi-UiO-66 composite material according to claim 2, characterized in that: In the step S12: the stirring reaction time is 2 to 6 hours.
5. The method for preparing the Au@quasi-UiO-66 composite material according to claim 1, characterized in that: In step S2: The mass ratio of the ionic liquid to the porous nanocarbon material is 0.05 to 0.15; The solvent is stirred at a temperature of 10 to 40°C for 18 to 24 hours; The metal salt is dissolved in the solvent by ultrasound, and the ultrasound time is 5 to 30 minutes.
6. The method for preparing the Au@quasi-UiO-66 composite material according to claim 1, characterized in that: In the step S2, the mass ratio of the ionic liquid to the porous nano-carbon material is 0.05 to 0.
125.
7. The method for preparing the Au@quasi-UiO-66 composite material according to claim 1, characterized in that: In step S3: The mixing time is 18 to 24 hours, and the temperature is 10 to 40°C; The rotary evaporation temperature is 50-70°C and the rotary evaporation time is 1-2h; The drying is vacuum drying, and the vacuum drying temperature is 60-100°C.
8. The method for preparing the Au@quasi-UiO-66 composite material according to claim 1, characterized in that: In step S4, the pyrolysis temperature is 325-450° C., and the pyrolysis time is 1-4 hours.
9. An Au@quasi-UiO-66 composite material, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. Use of the Au@quasi-UiO-66 composite material as claimed in claim 9 in the photocatalytic cycloaddition reaction of CO2 and epoxide at room temperature.
Citation Information
Patent Citations
Preparation and application of thiol-modified metal-organic framework catalysts
CN107233924B
MOF-packaged superfine alloy nano-particle as well as preparation method and application thereof
CN112871167A
A method for preparing a UiO-66 defect-site induced single-atom supported catalyst and its application
CN113769789B
Cited By
Bimetal carbon dioxide capture and methanation catalytic material as well as preparation method and application thereof
CN121911504A